Analysis of the thinking process of pharmacists in response to changes in the dispensing environment using the eye-tracking method - Toshikazu Tsuji; Kenichiro Nagata; Keiichi Sasaki; Ryosuke Matsukane; Shigeru Ishida; Takehiro Kawashiri; Kimitaka Suetsugu; Hiroyuki Watanabe; Takeshi Hirota; Ichiro Ieiri (BMC, 2022)
Abstract Background Pharmacists must understand the mechanisms by which dispensing errors occur and take appropriate preventive measures. In this study, the gaze movements of pharmacists were analyzed using an eye-tracking method, to elucidate the thinking process of pharmacists when identifying target drugs and avoiding dispensing errors. Methods We prepared verification slides and projected them on a large screen. Each slide comprised a drug rack area and a prescription area; the former consisted of a grid-like layout with 55 drugs and the latter displayed dispensing information (drug name, drug usage, location number, and total amount). Twelve pharmacists participated in the study, and three single-type drugs and six double-type drugs were used as target drugs. We analyzed the pharmacists' method of identifying the target drugs, the mechanisms by which errors occurred, and the usefulness of drug photographs using the error-induction (−) /photo (+), error-induction (+) / (+), and error-induction (+) /photo (−) models. Results Visual invasion by non-target drugs was found to have an effect on the subsequent occurrence of dispensing errors. In addition, when using error-induction models, the rate of dispensing error was 2.8 and 11.1% for the photo (+) and photo (−) models, respectively. Furthermore, based on the analysis of eight pharmacists who dispensed drugs without errors, it was clear that additional confirmation of "drug name" was required to accurately identify the target drug in the photo (+) model; additionally, that of "location number" was required to pinpoint directly the position of target drug in the photo (−) model. Conclusions By analyzing the gaze movements of pharmacists using the eye-tracking method, we clarified pharmacists' thinking process which was required to avoid dispensing errors in a complicated environment and proved the usefulness of drug photographs in terms of both reducing the complexity of the dispensing process and the risk of dispensing errors. Effective measures to prevent dispensing errors include ensuring non-adjacent placement of double-type drugs and utilization of their image information.